Association between body composition and clinical-subcinical features in female patients with primary knee osteoarthritis - Nguyen , Hoang Thanh Van; Nguyen , Tien Manh; Nguyen , Dinh Huan (Tạp chí Y Dược Huế, 2026)
Background: Fat mass is negatively associated while muscle mass is positively associated with knee osteoarthritis (KOA). This revised study investigates body composition and its relationship with clinicalsubclinical characteristics in Vietnamese female patients with primary KOA, addressing all reviewer comments. Methods: A cross-sectional study of 72 women meeting ACR 1991 criteria was conducted. Body composition was measured via DEXA, including total fat mass, body fat percentage (BF%), visceral adipose tissue (VAT), total muscle mass, appendicular skeletal muscle mass index (ASMI), and lower limb muscle index (LMI). Pain, function, and quality of life were assessed using WOMAC pain, WOMAC physical function, and HAQ-II. Spearman correlation, normality testing, and multivariable linear regression were applied. Results: Mean BF% was 40.62 ± 3.73%, with obesity prevalence of 55.6% using BF% ≥ 40% (equivalent to BMI ≥ 27.5 per Ho-Pham). A total of 25% of patients had low ASMI (≤ 5.4 kg/m² per AWGS 2019). BF% and VAT positively correlated with WOMAC pain (r=0.47 and r = 0.29). LMI and ASMI negatively correlated with pain, function, and HAQ-II. Regression showed BF% independently associated with WOMAC pain, while ASMI was associated with WOMAC pain and function. Radiographic severity (KL grade) was significantly associated with VAT and BF%. Conclusions: Increased fat mass worsens symptoms and radiographic severity, while reduced muscle mass impairs function and quality of life. Screening for obesity and muscle loss using DEXA is recommended in primary KOA patients.